2015
DOI: 10.1007/s10072-015-2414-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of the COQ2 V393A variant with risk of multiple system atrophy in East Asians: a case–control study and meta-analysis of the literature

Abstract: Recent studies in Japan have associated multiple system atrophy (MSA), a neurodegenerative disease of uncertain etiology, with polymorphism in the COQ2 gene. This led us to explore whether the same polymorphism is associated with MSA in Han Chinese and more broadly in East Asians. We conducted a case-control study with 82 Han Chinese with probable MSA and 484 gender- and age-matched healthy subjects, genotyping them using the ligase detection reaction. The results were meta-analyzed together with data from fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…in an unchanged diagnostic interpretation in 58 of 76 cases (76%), and reclassification in the remaining 18 cases (24%, Previously reported as a risk variant for multiple system atrophy (Zhao et al, 2016).…”
Section: Reanalysis Of Variants From the Original Cohort At 5 Years Rmentioning
confidence: 94%
“…in an unchanged diagnostic interpretation in 58 of 76 cases (76%), and reclassification in the remaining 18 cases (24%, Previously reported as a risk variant for multiple system atrophy (Zhao et al, 2016).…”
Section: Reanalysis Of Variants From the Original Cohort At 5 Years Rmentioning
confidence: 94%
“…1 Heterozygous mutations of COQ2 , in particularly the V393A mutation, are genetic risk factors for sporadic MSA in Japan but not in Europe or North America. Follow-up studies confirmed the association of COQ2 with MSA in a Taiwanese cohort and a Chinese cohort, 2,3 but the association was not replicated in other studies from East Asia. 4-6 Other European and North American studies also did not find the association between COQ2 mutations and MSA.…”
mentioning
confidence: 70%
“…A meta-analysis of East Asian cohorts (Japan, Taiwan, Korea, and China) supports the association of COQ2 mutations and MSA. 3 Indeed, patients with MSA in different geographic regions have diverse clinical presentations: Japanese patients have primarily the cerebellar subtype, whereas European patients have mostly the parkinsonism subtype. Consistent with this finding, COQ2 mutations seem to be more common in patients with the cerebellar subtype of MSA.…”
mentioning
confidence: 99%
“…An association between sporadic MSA and CoQ2 variants was found in Japanese, Taiwanese and Chinese populations, but these results were not replicated in other cohorts. [26][27][28][29][30][31] Further studies have revealed reduction in CoQ10 levels in the cerebellum and serum of patients with MSA. 32,33 These findings may be particularly important in implicating CoQ10 supplementation as a therapeutic option in MSA, though this has not yet been systematically studied.…”
Section: Coenzyme Q2 Genementioning
confidence: 99%